PERAN GURU PAI DALAM MEMBANGUN KESADARAN ETIKA KOMUNIKASI DI ERA DIGITAL: STUDI KASUS DI SMA ASSYAFIIYAH PADA KELAS 10 - Mohammad Dzaky Zaidan; Muhammad Abdul Khafi, Alfina Meiza Fasya, Salsabila, Suci Dwi Aprilia (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study explores the role of Islamic Religious Education (PAI) teachers in building students' communication ethics awareness in the digital era, focusing on grade 10 students at Assyafiiyah High School. The digital era brings new challenges, such as the spread of hoaxes, hate speech, and online bullying, which are often fuelled by anonymity in cyberspace. PAI teachers have a strategic role as moral mentors in integrating religious values with digital literacy to shape student character. This study used mixed methods combining qualitative and quantitative approaches through observation, interviews, questionnaires, and literature studies. The results showed that students' understanding of Islamic communication ethics has a significant positive relationship with the impact of Islamic education on their awareness. The teaching strategies applied include integrating religious values in learning, modeling, case studies, wise use of digital media, and personal approach and counselling. School policies such as the prohibition of playing mobile phones during class also positively impact students' character building. This research confirms the importance of religious value-based education as an effective solution to face communication challenges in the digital era and form a generation with noble character.